Responses to COVID-19 in South Asian Association for Regional Cooperation (SAARC) countries in 2020, a data analysis during a world of crises. (November 2021) - Malik, Yashpal Singh; Obli Rajendran, Vinodhkumar; MA, Ikram; Pande, Tripti; Ravichandran, Karthikeyan; Jaganathasamy, Nagaraj; Ganesh, Balasubramanian; Santhakumar, Aridoss; Tazerji, Sina Salajegheh; Rahman, Md. Tanvir; Safdar, Muhammad; Dubal, Zunjar B; et al.
Highlights: The current data found that the estimated Rt for COVID-19 in SAARC countries is around 0.90, with a range of 0.83 – 1.08. The overall decline in the Rt value suggested a lower death rate and an improvement in the control of the pandemic using lockdown, limited gathering and maintaining social distancing. COVID-19 deaths and health expenditure (% GDP) depicted significant positive correlation (r=0.58, p<0.05). The other factors such as population density/ Sq km, literacy %, adult population %, and poverty % are not significantly correlated with COVID-19 cases and deaths (p>0.05). Abstract: Coronavirus disease (COVID-19) caused by SARS-CoV-2 was notified from Wuhan city, Hubei province, China in the mid of December 2019. The disease is showing dynamic change in the pattern of confirmed cases and death toll in these low and middle-income countries (LMICs). In this study, exponential growth (EG) method was used to calculate the real-time reproductive number (Rt ) for initial and later stage of epidemic in South Asian Association for Regional Cooperation (SAARC) member countries (April 2020 – December 2020). Time dependent (TD) method was used to calculate the weekly real-time reproduction number (Rt ). We also presented the observations on COVID-19 epidemiology in relation with the health expenditure, poverty, BCG vaccination, literacy population density and Rt for understanding the current scenario, trends, and expected outcome of the disease in SAARC countries. A significant positive correlation was noticed between COVID-19 deaths and health expenditure (% GDP) (r = 0.58, P  < 0.05). The other factors such as population density/sq km, literacy %, adult population %, and poverty % were not significantly correlated with number of COVID-19 cases and deaths. Among SAARC countries, the highest Rt was observed in India (Rt  = 2.10; 95% CI 2.04–2.17) followed by Bangladesh (Rt  = 1.62; 95% CI 1.59–1.64) in initial state of epidemic. A continuous monitoring is necessitated in all countries looking at the medical facilities, available infrastructure and healthcare manpower, constraints which may appear with increased number of critically ill patients if the situation persists longer.